Zoledronic acid as an adjuvant therapy in patients with breast cancer: a systematic review and meta-analysis. - Wei-Wei Huang; Cheng Huang; Jian Liu; Hong-Yu Zheng; Lin Lin (PLoS ONE, 2012)
Background Zoledronic acid is widely used as adjuvant chemotherapy for the treatment of breast cancer. However, previous trials reported inconsistent findings regarding their clinical efficacy and safety. We carried out a comprehensive systematic review and meta-analysis to evaluate the effects of zoledronic acid on disease-free survival (DFS), overall survival (OS), and drug-related toxicities. Methodology and principal findings We systematically searched Medline, EmBase, the Cochrane Central Register of Controlled Trials, reference lists of articles and proceedings of major meetings for relevant literatures with a time limit of Dec. 1, 2011. Randomized controlled trials evaluated the effects of zoledronic acid on OS, DFS, and RFS compared with control were eligible for inclusion in our research. Of 175 identified studies, we collected data from 7 randomized controlled trials of zoledronic acid that had OS, DFS, and RFS reported as one of the endpoint. Overall, we noted that patients receiving zoledronic acid therapy had significant longer OS than the group with non-zoledronic acid therapy (HR, 0.85, 95%CI, 0.73 to 1.00, P = 0.047). Furthermore, zoledronic acid therapy also had a clear effect on frature events (RR, 0.66, 95%CI, 0.52 to 0.84, P<0.001). Subgroup analysis indicated that zoledronic acid therapy showed a great beneficial effect on disease recurrence in patients with early-stage breast cancer, however, it also significantly increased the harm of disease recurrence in patients with advanced breast cancer. Bone pain, neutropenic fever, pyrexia, rash were more frequent in the zoledronic acid therapy group. Conclusion/significance Treatment with zoledronic acid had a clear effect on fracture events, and it might contribute an important role for overall survival.